Tratamentos biológicos na produção de mudas e produtividade de pimentão (Capsicum annuum L.) - Castro, Fernanda Ticianelli de (Universidade Federal de São Carlos, 2024)
Efficient alternatives to ensure plant nutrition and disease management are challenges for ecologically based agriculture, which does not use fertilizers minerals and conventional agricultural pesticides. One of the main crops in use of pesticides is pepper (Capsicum annuum L.), however, there are already on the market several biological inputs that can be used in the management of culture. Furthermore, there are agroecological techniques for capturing, selecting and reproduction of natural communities of efficient microorganisms present in nature that can also be used. The present study aimed to objective to compare the efficiency of mixed synthetic communities and strains isolated from commercially available biological products of Bacillus velezensis and Trichoderma sp., as well as natural communities of efficient microorganisms natives captured near the study area. Isolated microorganisms and two different types of microorganism communities were applied in trays, for the formation of seedlings, and in the field, in transplanted seedlings and evaluated parameters of growth, development and productivity of plants. It was possible to verify, for the experiment with seedling formation, emphasis on treatment with T. harzianum in all indicators of aerial part development (number of leaves, stem diameter, height and dry mass of aerial part). In plants in the field there was no difference between treatments in indicators of dry mass production and plant productivity.
Biological treatments in seedling production and crop productivity pepper (Capsicum annuum L.)
Keywords: Bioinsumos; Microrganismos eficientes; Agroecologia; Bioinputs; Efficient microorganisms; Agroecology; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA